Relationship between breast feeding duration and risk of overweight/obesity among Egyptian children - Nayera E. Hassan; Sahar A. El-Masry; Salwa R. El Batrawy; Aya Khalil; Manal M. Ali; Muhammad Al Tohamy; Maha Abo Hashish (SpringerOpen, 2018)
Background and aim: Breast feeding (BF); as risk factor for/or protective against childhood overweight/obesity; remains matter of debate. This study assesses relationship between BF duration, and development of overweight/obesity among Egyptian children, with respect for wide range of potentially confounding variables. Subjects and methods: Cross sectional-retrospective study included 154 children of both sexes; aged 6-18 years. Data was collected about child birth weight, breast feeding duration, and start of weaning, family size, parental ages, education, occupation and place of residence. Anthropometric measurements and body composition were conducted. Children were classified into 3 age groups (6-9, 9.1-12 and 12.1-18 years) and 4 groups according to BF duration (Never BF, BF for 6, 7-12, and more than 12 months). Results: Children who never BF were12.8%, while those BF for more than 12 months were 59.7%. Start of weaning was more common at 5-6 months of age (58.4%). Overweight/Obesity was detected among 30.5% of children. It was more prominent among children who BF for more than 12 months in ages 6-12 years (64.3% and 71.4%), while in those aged 12-18 years it was equivalent in those never BF (33.3%) and who BF for more than 12 months (38.9%). BF duration had insignificant correlations with parental education or occupation, or with any of the child's anthropometric measurements. Conclusion: Childhood overweight/obesity were less prominent among children who Bf for <12 months; However, there was no effect of breast feeding duration on any of the child anthropometric measures.